Public Debt Asymmetries and Tax Competition - Signe Krogstrup (University of Copenhagen, Economic Policy Research Unit (EPRU), 2004)
The paper investigates the effect of asymmetric debt and debt servicing obligations on taxes and primary spending in a standard tax competition model, assuming public debts are pre-determined and in their steady state. The impact of increasing financial market integration and capital mobility on tax and spending asymmetries is then investigated, and the results are tested empirically for EU countries. The model predicts that cross country asymmetries in debt servicing obligations lead to cross-country asymmetries in taxes and spending, and these predictions are supported by the data, with high-debt EU countries having lower expenditures and higher taxes than low-debt countries. Moreover, as the impact of increasing capital mobility on tax asymmetries is theoretically ambiguous and empirically insignificant, increasing capital mobility is found to amplify debt-induced tax distortion asymmetries. Finally, higher capital mobility is found to amplify public spending asymmetries theoretically as well as empirically across EU member countries.
Keywords: H2; H6; F2; 330; public debt; tax competition; European integration; Steuerwettbewerb; Öffentliche Schulden; Kapitalmobilität; Theorie; EU-Staaten